When the Going Gets Tough: The Impact of Health Shocks on Divorce - Javier Adrián López Artero; Anna Sanz-de-Galdeano; Daniela Vuri (Institute of Labor Economics (IZA), 2025)
We analyze the impact of unexpected health shocks–defined as the sudden diagnosis of cancer, stroke, or heart attack–on the probability of couple dissolution using longitudinal representative data on older individuals (50+). We leverage the longitudinal nature of the HRS and utilize a quasi-experimental research approach that creates counterfactual scenarios for affected households by comparing them to households set to experience the same event in subsequent years. We find that experiencing a health shock significantly increases the probability of couple dissolution by approximately 19% of the mean divorce prevalence. This effect intensifies gradually over time rather than appearing immediately after the adverse health event. Additionally, we examine several mechanisms through which health shocks may influence divorce, focusing on three potential channels: mental health, cognitive decline, and financial strain. Our findings suggest that all three mechanisms likely play a role in mediating the relationship between health shocks and the increased probability of divorce.
Keywords: I14; I24; J15; Z13; J13; 330; divorce; health shocks; aging